Contrasting precipitation seasonality influences evapotranspiration dynamics in water‐limited shrublands. Issue 2 (18th February 2016) - Villarreal, Samuel; Vargas, Rodrigo; Yepez, Enrico A.; Acosta, Jose S.; Castro, Angel; Escoto‐Rodriguez, Martin; Lopez, Eulogio; Martínez‐Osuna, Juan; Rodriguez, Julio C.; Smith, Stephen V.; Vivoni, Enrique R.; Watts, Christopher J.
Abstract: Water‐limited ecosystems occupy nearly 30% of the Earth, but arguably, the controls on their ecosystem processes remain largely uncertain. We analyzed six site years of eddy covariance measurements of evapotranspiration (ET) from 2008 to 2010 at two water‐limited shrublands: one dominated by winter precipitation (WP site) and another dominated by summer precipitation (SP site), but with similar solar radiation patterns in the Northern Hemisphere. We determined how physical forcing factors (i.e., net radiation ( Rn ), soil water content (SWC), air temperature ( Ta ), and vapor pressure deficit (VPD)) influence annual and seasonal variability of ET. Mean annual ET at SP site was 455 ± 91 mm yr −1, was mainly influenced by SWC during the dry season, by Rn during the wet season, and was highly sensitive to changes in annual precipitation ( P ). Mean annual ET at WP site was 363 ± 52 mm yr −1, had less interannual variability, but multiple variables (i.e., SWC, Ta, VPD, and Rn ) were needed to explain ET among years and seasons. Wavelet coherence analysis showed that ET at SP site has a consistent temporal coherency with Ta and P, but this was not the case for ET at WP site. Our results support the paradigm that SWC is the main control of ET in water‐limited ecosystems when radiation and temperature are not the limiting factors. In contrast, when P and SWC are decoupled from available energy (i.e., radiation and temperature), then ET is controlled by an interaction of multiple variables. Our results bring attention to the need for better understanding how climate and soil dynamics influence ET across these globally distributed ecosystems. Key Points: Evapotranspiration (ET) dynamics were compared at two water‐limited shrublands Precipitation seasonality influenced relationships between ET and forcing variables Soil moisture is the main control of ET when radiation and temperature are not limiting